2019
DOI: 10.1038/s41598-019-42576-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated carbon dioxide levels lead to proteome-wide alterations for optimal growth of a fast-growing cyanobacterium, Synechococcus elongatus PCC 11801

Abstract: The environmental considerations attributing to the escalation of carbon dioxide emissions have raised alarmingly. Consequently, the concept of sequestration and biological conversion of CO 2 by photosynthetic microorganisms is gaining enormous recognition. In this study, in an attempt to discern the synergistic CO 2 tolerance mechanisms, metabolic responses to increasing CO 2 concentrations were determined for Synechococcus elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 85 publications
1
22
0
Order By: Relevance
“…Another protein that showed greater expression in nutritional limitation, with under expression in the control, is a glyceraldehyde-3-phosphate dehydrogenase, and in this group there is also a glyceraldehyde-3-phosphate dehydrogenase with similar expression in both conditions; this protein is associated with carbon fixation [ 96 ] and is essential to the Calvin cycle in the catabolic degradation of glucose [ 97 , 98 ]. It is an important biotechnological hub for the production of Isopentenyl pyrophosphate (IPP) and 4-Dimethylaminopyridine (DMAP) for terpenes biosynthesis, 3-hydroxypropionic acid [ 99 ] and lipids [ 100 ] including PHB [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another protein that showed greater expression in nutritional limitation, with under expression in the control, is a glyceraldehyde-3-phosphate dehydrogenase, and in this group there is also a glyceraldehyde-3-phosphate dehydrogenase with similar expression in both conditions; this protein is associated with carbon fixation [ 96 ] and is essential to the Calvin cycle in the catabolic degradation of glucose [ 97 , 98 ]. It is an important biotechnological hub for the production of Isopentenyl pyrophosphate (IPP) and 4-Dimethylaminopyridine (DMAP) for terpenes biosynthesis, 3-hydroxypropionic acid [ 99 ] and lipids [ 100 ] including PHB [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a previous study found no difference in photosynthetic rate between Triodia pungens plants grown in ambient or eCO 2 concentration; in which case, eCO 2 resulted in lower g s and Tr, improved WUE, and higher dry biomass [32]. However, studies have also shown that plants often show photosynthetic down-regulation under long-term eCO 2 exposure, while biomass production may change and even decrease due to species-speci c responses to different durations of treatment exposure [33,34]. A high CO 2 concentration resulted in reduced RubisCo concentration, and both photosynthesis and photorespiration decreased to maintain substrate concentrations [35].…”
Section: Physiological Response To Ecomentioning
confidence: 98%
“…In the LT cells, genes encoding the transcript of nitrate/nitrite transporter (NRT), which transports extracellular nitrate/ nitrite into cells, were notably downregulated. Subsequently, nitrate is taken up into algal cells, where it is first reduced to nitrite by NADH-dependent nitrate reductase (NR) and further reduced to ammonium by ferredoxin nitrite reductase (Fd-NiR) (Allen et al 2005;Bowler et al 2010;Mehta et al 2019). There are two ways for ammonium assimilation, one is to form carbon skeletons via the GS-GOGAT pathway and the other is to generate carbamoyl-phosphate by carbamoyl-phosphate synthase (CPS) (Fig.…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
“…Genes involved in nitrogen metabolism significantly change in cells under LT but no significant change was found in cells under ST (Table 3). In Synechococcus elongates, the elevated expression of NrtA, NrtC (a nitrate transport ATP-binding protein), glutamate synthase (ferredoxin), glutamine synthetase III, glutamine synthetase, and ferredoxin-nitrite reductase was observed in a possible effort to maintain the homeostasis of C:N ratio at high CO 2 (Mehta et al 2019). Furthermore, metabolic analysis showed that L-glutamate and L-proline were significantly downregulated in LT vs CK (Table 2).…”
Section: Nitrogen Metabolismmentioning
confidence: 99%